Penanganan Kasus Langka Fistula Trakeoesofagus Ganda Tipe D yang Parah di Lingkungan Pedesaan dengan Sumber Daya Terbatas: (Laporan Kasus) - Maulfi Natsir Asy’ari; Tinton Candra Saputra; Herjunanto Nur Priyadi; Robin Perdana Saputra (Jurnal Sains dan Kesehatan, 2026)
Esophageal atresia with tracheoesophageal fistula is a congenital anomaly requiring early diagnosis and prompt surgical correction. Gross type D esophageal atresia, characterized by both proximal and distal tracheoesophageal fistulas, is an exceedingly rare variant that poses significant diagnostic and operative challenges. We report a case of a full-term female neonate with a birth weight of 3,200 grams who presented with hypersalivation since the first day of life, accompanied by coughing and choking during feeding. Orogastric tube insertion failed, with the tube arrested at approximately 15 cm. The patient was referred with a diagnosis of neonatal pneumonia and suspected esophageal atresia with tracheoesophageal fistula. Physical examination revealed tachypnea, chest wall retraction, and respiratory distress requiring ventilatory support. Babygram demonstrated the orogastric tube tip arrested at the proximal esophageal pouch with distal gastrointestinal air. Contrast esophagography confirmed proximal esophageal atresia at the upper thoracic level with suspected proximal fistula. Associated findings included bilateral pneumonia, right upper lobe atelectasis, and vertebral anomalies suggestive of VACTERL association. Intraoperative findings confirmed Gross type D esophageal atresia with proximal and distal tracheoesophageal fistulas. Both fistulas were excised, followed by primary esophageal anastomosis and transanastomotic nasogastric tube placement. Gross type D esophageal atresia is a rare congenital anomaly that should be considered in neonates presenting with hypersalivation, failed orogastric tube insertion, and respiratory distress. Anatomical subtype confirmation relies on intraoperative findings. Early surgical repair can be performed successfully; however, associated anomalies necessitate careful long-term follow-up.